Α‐Mangostin protects lipopolysaccharide‐stimulated nucleus pulposus cells against NLRP3 inflammasome‐mediated apoptosis via the NF‐κB pathway. Issue 9 (27th February 2022) - Chen, Jingyang; Bian, Meiru; Pan, Lingxiao; Yang, Hanshi
Abstract: Intervertebral disc degeneration (IDD) is a common and chronic inflammatory disorder. α‐Mangostin exhibits a novel biological function against inflammation in various inflammatory diseases. Here, we aimed to explore the role of α‐mangostin in IDD using an in vitro cell model. Human nucleus pulposus cells (NPCs) were exposed to lipopolysaccharide (LPS) to induce inflammatory injury. Cell viability of NPCs was determined by CCK‐8 assay. ELISA was performed to examine the production of interleukin (IL)‐1β and IL‐18. Apoptotic cell death in NPCs was detected by TUNEL staining. The expression levels of apoptotic‐associated proteins were detected by western blotting. Nuclear factor‐kappa B (NF‐κB) activation was examined by determining the expression levels of p‐p65, p65, and nuclear p65. Results showed that treatment with α‐mangostin improved the viability of LPS‐treated NPCs. α‐Mangostin treatment also inhibited the LPS‐induced increase in expression levels of NLRP3, ASC and pro‐caspase‐1, as well as the production of IL‐1β and IL‐18 in NPCs. Moreover, treatment with α‐mangostin or NLRP3 inhibitor (MCC950) significantly decreased apoptotic cell death in NPCs, as compared with treatment with LPS. In addition, the expression levels of cleaved caspase‐3 and Bax were decreased, while Bcl‐2 expression was increased in α‐mangostin‐ or MCC950‐treated NPCs. Treatment with α‐mangostin also suppressed LPS‐induced increase of p‐p65/p65 and nuclear p65 levels. Moreover, inhibition of NF‐κB by PDTC aggravated the inhibitory effects of α‐mangostin on NLRP3 inflammasome activation and apoptosis in LPS‐induced NPCs. These findings suggested that α‐mangostin exerted a protective effect on NLRP3 inflammasome‐mediated apoptosis in LPS‐induced NPCs through regulating NF‐κB signaling. Abstract : α‐Mangostin exhibits a novel biological function against inflammation in various inflammatory diseases. Herein, we aimed to explore the role of α‐mangostin in intervertebral disc degeneration (IDD) using an in vitro cell model. Our data showed that α‐mangostin exerted a protective effect on NLRP3 inflammasome‐mediated apoptosis in LPS‐induced NPCs through regulating NF‐κB signaling. This indicates that α‐mangostin may have a protective effect against IDD and may potentially serve as a clinical agent for IDD prevention and treatment.